2001
DOI: 10.1271/bbb.65.1645
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition by Agaricus blazei Murill Fractions of Cytopathic Effect Induced by Western Equine Encephalitis (WEE) Virus on VERO Cells in Vitro

Abstract: Anti-viral activities of Agaricus blazei Murill were investigated. The water extracts of the cultured mycelia and fruiting bodies were fractionated with different concentrations of ethanol. To several viruses which have cytopathic effects (CPE) on VERO cells, inhibition of these effects by the ethanol fractions was tested. Strong inhibition of CPE induced by western equine encephalitis (WEE) virus was observed in the mycelial fractions but not those of fruiting bodies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
53
1
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(57 citation statements)
references
References 8 publications
2
53
1
1
Order By: Relevance
“…Zhu et al (20) demonstrated that a sulphated polysaccharide isolated from alga Sargassum patens inhibited up to 96% the formation of plaques in Vero cells (African green monkey kidney cells) infected by HSV-2 (20). Sorimachi et al (19) showed that aqueous extract and fractions obtained by alcoholic extraction of A. blazei Murill were able to inhibit the cytopathic effect of Western Equine Encephalitis (WEE) virus, poliovirus and HSV in cultures of Vero cells (19). The authors demonstrated a greater activity of the alcoholic fractions in comparison to the aqueous extract, however these effect were demonstrated in therapeutic protocol.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Zhu et al (20) demonstrated that a sulphated polysaccharide isolated from alga Sargassum patens inhibited up to 96% the formation of plaques in Vero cells (African green monkey kidney cells) infected by HSV-2 (20). Sorimachi et al (19) showed that aqueous extract and fractions obtained by alcoholic extraction of A. blazei Murill were able to inhibit the cytopathic effect of Western Equine Encephalitis (WEE) virus, poliovirus and HSV in cultures of Vero cells (19). The authors demonstrated a greater activity of the alcoholic fractions in comparison to the aqueous extract, however these effect were demonstrated in therapeutic protocol.…”
Section: Discussionmentioning
confidence: 99%
“…Popularly, this fungus is used against physical and mental stress, osteoporosis and gastric ulcer, as stimulatory of immunity and for cholesterol reduction. It is also used as antioxidant, antimutagenic, and anticarcinogenic (5,8,10,12,19). Sorimachi et al (19) also demonstrated that A blazei inhibited the cytopathic effect of Western Equine Encephalitis Virus.…”
Section: Introductionmentioning
confidence: 99%
“…The antitumour effects of AbM components have been documented in mouse models and cancer cell cultures [9][10][11]. AbM mycelium has also been shown to inhibit the cytopathic effects of Western equine encephalitis virus on VERO cells in culture [12], and in vitro bactericidal and fungicidal effects of Agaricus sp. have been reported [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…Various A. blazei extracts obtained using different solvents have been evaluated and the protective potential of compounds present in these extracts has been the subject of much published research, some by our group (Delmanto et al, 2001;Menoli et al, 2001;Luiz et al, 2003a;Machado et al, 2005;Bellini et al, 2006) and some by other researchers (Sorimachi et al, 2001;Kasai et al, 2004).…”
Section: Introductionmentioning
confidence: 99%